Nuclear envelope localization of an adenovirus tumor antigen maintains the integrity of cellular DNA. - White, E (1984)
The adenovirus early-region 1B 19,000-molecular-weight tumor antigen is required for oncogenic transformation of cells by adenovirus. We have demonstrated that this tumor antigen is located in the nuclear envelope of infected and transformed cells and that a fraction of the protein within the nuclear envelope is associated with the nuclear lamina. During cell division in the transformed cells, the nuclear envelope containing the tumor antigen dissociates at metaphase and then reforms around the separated daughter chromosomes at telophase. Adenovirus mutants carrying lesions in the gene encoding this tumor antigen cause degradation of host cell chromosomal DNA, and in these mutants, the intracellular localization of the 19,000-dalton protein is altered. These results demonstrate that components of the nuclear envelope function in the organization of chromatin in infected and transformed cells and that a virus-encoded protein plays a critical role in this process.